Impact of macroeconomic factors on inclusiveness in outpatient service use in Vietnam in the period 2008-2022 - Nguyet, Bui Thi Minh; Bao, Ho Dinh; Nguyen, Vu Duy; Khanh, Pham Van (Edelweiss Applied Science and Technology, 2025)
This study analyzes the impact of factors on the inclusiveness of outpatient service use in Vietnam from 2008 to 2022 based on data from 63 provinces and cities nationwide. The study applies the social opportunity function method to measure the level of inclusiveness in health service use in Vietnam and analyzes the impact of economic factors, macroeconomic policies, and public spending based on provincial data. Using fixed effects, random effects, and FGLS (Feasible Generalized Least Squares) estimation methods, the study considers economic, social, and health policy factors to assess their influence on people's access to and use of health services. The study results indicate that factors such as inclusive growth, health budgets, and appropriate allocation of health resources play an important role in expanding and improving access to health services, especially outpatient services. However, the study also found that current health support policies have not been as effective as expected, possibly due to lack of coordination between government levels or failure to meet the actual needs of the people.